Bridging the gap between de jure and de facto parliamentary representation of women in Africa : lessons from Rwanda and South Africa - Twinomugisha, Ben (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2006.